Durability of concrete members reinforced with steel-FRP composite bars under dry-wet cycles of seawater. (October 2021) - Ding, Lining; Lei, Mengke; Wang, Xin; Shi, Yuwei; Zhu, Zhongguo; Yu, Pancheng; Wu, Zhishen
Highlight: Examined the bond behavior between SFCB and concrete and flexural behavior SFCB reinforced beams under wet-dry cycles. Presented a formula for the degradation of the strength of SFCB in a concrete-wrapped environment under dry-wet cycles. Derived the bond-dependent coefficient of SFCB under wet-dry cycles. Abstract: To complete durability research on concrete members reinforced with steel-FRP composite bars (SFCBs), this paper examines the flexural behavior of these type of members conditioned with wet-dry cycles. The bonding and flexural behaviors of concrete members with changes in dry and wet cycling time, which were reinforced with steel bars and SFCBs, were compared by pullout tests and four-point bending tests, and beams were precracked before conditioning. The pullout specimens and bending specimens failed in the design mode of reinforcement pull-through and concrete crushing, respectively, and there were no changes as the condition time increased. The test results indicated that the maximum bond stress, stiffness and ductility of the SFCB-reinforced members increased as the age increased, whereas the characteristic loads and ability to control cracks weakened. Compared with RC members, SFCB-RC members performed better in terms of stiffness, capacity and crack control. The SFCB could be simplified as an FRP bar to calculate the flexural capacity, and the bond-dependent coefficient k b was equal to 1.10. For corrosion SFCB-RC beams with a short corrosion time, k b is less than 1.0.